Introductory statistics for the behavioral sciences - Welkowitz, Joan.; Cohen, Barry H., 1949-; Lea, R. Brooke; ebrary, Inc. (Hoboken, N.J. : Wiley, 2012)
"This popular and well-respected statistics text has been thoroughly revised to present all the topics behavioral science students need. Now featuring expanded Web sites for instructors and students, the authors provide a framework that connects all of the topics in the text and allows for easy comparison of different statistical analyses. Refined over seven editions by master teachers, this book gives instructors and students alike the well laid out examples and exercises to support the teaching and learning of statistics for both manipulation and consumption of data"--
Machine generated contents note: Part I Descriptive Statistics Chapter 1: Introduction Chapter 2: Frequency Distributions and Graphs Chapter 3: Measures of Central Tendency and Variability Chapter 4: Standardized Scores and the Normal Distribution Part II Basic Inferential Statistics Chapter 5: Introduction to Statistical Inference Chapter 6: The One-Sample t Test and Interval Estimation Chapter 7: Testing Hypotheses about the Difference between the Means of Two Populations Chapter 8: Nonparametric Tests for the Difference between Two Means Chapter 9: Linear Correlation Chapter 10: Prediction and Linear Regression Chapter 11: Introduction to Power Analysis Part III Analysis of Variance Methods Chapter 12: One-Way Analysis of Variance Chapter 13: Multiple Comparisons Chapter 14: Introduction to Factorial Design: Two-Way Analysis of Variance Chapter 15: Repeated-Measures ANOVA Part IV Nonparametric Statistics for Categorical Data Chapter 16: Probability of Discrete Events and the Binomial Distribution Chapter 17: Chi Square Tests Appendix Glossary of Terms.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Social sciences -- Statistical methods; Psychometrics; Sociology -- Statistical methods; Educational statistics; Electronic books